The paradox of functional heterochromatin. - Dimitri, P.; Corradini, N.; Rossie, F.; Verni, F. (BioEssays, 2005)
Although heterochromatin has been studied for 80 years, its genetic function and molecular organization have remained elusive. In almost all organisms, heterochromatin has been regarded as genetically inactive chromosome regions. However, from genetic and genomic studies in Drosophila melanogaster and other organisms including humans, it is now clear that transcriptionally active domains are present within constitutive heterochromatin. These domains contain essential coding genes whose expression during development ensures the formation of the proper biochemical and morphological phenotypes, together with several gene models defined by genome annotation whose functions still need to be determined.